2020
DOI: 10.1177/2633366x20912440
|View full text |Cite
|
Sign up to set email alerts
|

Study on ice adhesion of composite anti-/deicing component under heating condition

Abstract: An anti-/deicing component of composite materials for wind turbine blades is usually carried out under heating conditions. In order to study the ice adhesion properties of composite anti-/deicing component under heating conditions, an experimental platform for measuring ice adhesion force on composites was set up. Based on the heating parameters such as the heating temperature, heating voltage, and heating time, the experiments of ice adhesion of composite anti-/deicing component under deicing conditions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Undesired ice accumulation is problematic in industries such as renewable energy (wind turbines 1 , 2 , hydroelectric dams 3 ), aviation 4 , and power transmission 5 . Ice mitigation strategies can be divided into either active or passive methods.…”
Section: Introductionmentioning
confidence: 99%
“…Undesired ice accumulation is problematic in industries such as renewable energy (wind turbines 1 , 2 , hydroelectric dams 3 ), aviation 4 , and power transmission 5 . Ice mitigation strategies can be divided into either active or passive methods.…”
Section: Introductionmentioning
confidence: 99%
“…Variation in heating time suggest that the total initial ice adhesion force F on ice/surface interface may have changed and the residual adhesion force F o can be calculated as [48]:…”
Section: Effect Of Heating At the Ice/solid Interfacesmentioning
confidence: 99%
“…To tackle this problem, Zhang conducted preliminary research for composite materials, in which ice adhesion forces were measured under various heating temperatures, heating voltages, and heating times. The aluminum substrate was not included in his study [32]. It was found that more energy consumption leads to more adhesion strength reduction.…”
Section: Introductionmentioning
confidence: 99%